MENINGKATKAN KEMAMPUAN GURU MELAKSANAKAN MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE STAD DI MTsN PEMATANGSIANTAR - Hasibuan, M. Idrus (IAIN PADANGSIDIMPUAN, 2013)
Students’ interest towards study, exercising motivation building, and interesting study are goals for appropriate study model. Hopefully, it will cause students to get a better result of study.Robert Slavin and colleagues find cooperative learning type that is students’ team achievements division (STAD). It is suitable for those who want to start using the type in study. Meaning, the type encourages students to improve study motivation, study result improvement, and study retention improvement